A survey study of endometrial receptivity tests and immunological treatments in in vitro fertilisation (IVF). (4th December 2021) - Kieu, Violet; Lantsberg, Daniel; Mizrachi, Yossi; Stern, Catharyn; Polyakov, Alex; Teh, Wan Tinn
Abstract : Background: Suboptimal endometrial receptivity is a key factor behind in vitro fertilisation (IVF) implantation failure. Direct clinical tests of the endometrium of natural killer (NK) cells and endometrial receptivity analysis (ERA) are controversial. Aims: To examine the current practice of endometrial receptivity tests (NK cells and ERA) and immunological treatments (corticosteroids, anticoagulants, antiplatelets, intravenous immunoglobulin, Intralipid, other) among fertility specialists in Australia and New Zealand. Methods: A prospective 23‐item web‐based survey was distributed by email via the Fertility Society of Australia and New Zealand, between August and October 2020. Data were collected and analysed using Qualtrics. Results: Of 238 fertility specialists, 90 completed the survey (response rate 37.8%). ERA (48/90, 53.3%) was most commonly ordered, followed by uterine NK (uNK) (36/90, 40.0%) and peripheral blood NK (pNK) (12/90, 13.3%). For all tests, the most common indication was recurrent implantation failure (RIF) (41/48, 22/36, 6/12; 85.4%, 61.1%, and 50.0%, respectively for ERA, uNK and pNK). Of those that did not offer these tests, the main reason cited was insufficient evidence (30/42, 47/54, 68/78; 71.4%, 87.0%, and 87.0%). A third of specialists offered empirical immunological treatment for RIF (30/90, 33.3%): anticoagulants (28/30, 93.3%), antiplatelets (27/30, 90.0%), and corticosteroids (25/30; 83.3%). The majority of specialists (56/90, 62.2%) stated they had refused a patient request for endometrial testing or treatment. Conclusions: Tests for presumed endometrial receptivity pathology are often used in Australia and New Zealand. Immunological treatments for RIF are commonly employed empirically, without strong evidence of their effectiveness or safety. Further studies should focus on education and clinical adherence to evidence‐based guidelines.